PHYSIOLOGICAL STUDY OF THE STRATIFICATION EFFECT ON THE DYNAMIC CHANGES IN ENDOGENOUS ABSCISIC ACID IN BITTER ALMOND SEEDS (Prunus amygdalus L.) AND ITS RELATION TO SEEDS GERMINATION. - Nabil M. Ameen Al-Imam (Mesopotamia Journal of Agriculture)
Endogenous concentrations of free and bound abscisic acid (ABA) in bitter almond seeds Badam variety (local variety) from Sulaimania orchards Prunus amygdalus L. were determined by TLC and HPLC during various periods of cold stratification (0,15,30,45, and 60 days) and the germination was investigated at the Plant Hormones Laboratory in the Department of Plant Production, Faculty of Agriculture, University of Jordan, Amman, Jordan, during the period 2004 to 2005. The results indicated that cold stratification (at 5 ºC using perforated polyethylene bags filled with moistened perlite) significantly reduced abscisic acid (ABA) contents of the seeds and their endocarps. A sharp significantly decline in ABA was observed during the first 15 days, especially in 45 days, after that the decline was completely decreased. The reduction in the level of ABA during stratification was associated with significantly increased germination percentage especially for 45 days (85.133 %).